Social and environmental effects of large dams / by Edward Goldsmith and Nicholas Hildyard - Goldsmith, Edward; Hildyard, Nicholas (Cornwall, 1984)
This report is an attempt to provide an overview of the social and environmental effects of building large dams. three reports on this subject. The other two will provide, respect It is the first of timely, a collection of case-studies, and an annotated bibliography. They are due out in late 1984.
Keywords: Dams Environmental aspects